2006
DOI: 10.1038/sj.jcbfm.9600393
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in Mammalian Target of Rapamycin Signaling Pathways after Traumatic Brain Injury

Abstract: In response to traumatic brain injury (TBI), neurons initiate neuroplastic processes through the activation of intracellular signaling pathways. However, the molecular mechanisms underlying neuroplasticity after TBI are poorly understood. To study this, we utilized the fluid-percussion brain injury (FPI) model to investigate alterations in the mammalian target of rapamycin (mTOR) signaling pathways in response to TBI. Mammalian target of rapamycin stimulates mRNA translation through phosphorylation of eukaryot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
86
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 84 publications
(92 citation statements)
references
References 42 publications
5
86
1
Order By: Relevance
“…Phosphorylation of S6RP was previously described exclusively in neurons after TBI in rats, and was hypothesized to increase neuronal translational capacity (Chen et al, 2007). We also found neuronal expression of p-S6RP before and after CCI.…”
Section: Discussionmentioning
confidence: 60%
“…Phosphorylation of S6RP was previously described exclusively in neurons after TBI in rats, and was hypothesized to increase neuronal translational capacity (Chen et al, 2007). We also found neuronal expression of p-S6RP before and after CCI.…”
Section: Discussionmentioning
confidence: 60%
“…13 In two other CHI models, Akt phosphorylation was induced in the hippocampus between 1 and 24 hours in mice, 16 but only transiently at 1 hour after diffuse brain injury in rats, 27 whereas mTOR activation was reported from 30 minutes to 24 hours after fluid percussion in rats. 28 Thus, activation of Akt and mTOR is a generalized feature of TBI, 29 but their exact temporal course is model-specific.…”
Section: Discussionmentioning
confidence: 99%
“…6 The focus of the present study is on the PI3K/Akt/mTOR pathway, which other groups have shown to be strongly induced in vivo post-TBI. 7,8 The PI3K/Akt/mTOR signaling pathway is a major player in the control of cell size, dendrite and axon outgrowth during brain development, and repair. 9,10 Growth factors and hormones typically stimulate this pathway through the activation of receptor tyrosine kinases, leading to the activation of the PI3K and downstream Akt, which in turn regulates the activity of many signaling molecules, including mTOR.…”
mentioning
confidence: 99%